Supply Chain Cooperation by Agreed Reduction of Behavior Variability: A Simulation-based Study - Chew Hernandez, M. L.; Viveros Rosas, L.; Retes Mantilla, R. F.; Espinosa Martínez, G. J.; Velazquez Romero, V. (Engineering, Technology & Applied Science Research, 2017)
Supply chain echelons normally base their operational decisions on average values of the parameters that depend on other members. However, in real-life operation the variability of said parameters decreases the link profits. Thus, a cooperative arrangement may be devised in which a link agrees to reduce the variability of its behavior to enhance the performance of other links, receiving compensation in return. This work shows the application of simulation and decision trees to assess the feasibility of this cooperation scheme, from the perspective of the central link of a three member supply chain. First, the operational parameters of the link are optimized for mean values of the variables set by adjacent members. Then, by simulating the system for different probability distributions of these variables, graphs of the expected link gain versus the variances of the distributions are plotted. The results are incorporated to decision trees to evaluate the collaboration feasibility. It was found that the increased variability of the behavior of one neighboring member decreases the benefit of lowering the variability of the behavior of the other. The manuscript closes with a discussion of the practical viability of this collaboration scheme.